Playing by the Rules : Reforming Fiscal Governance in Europe - Eyraud, Luc (IMF Working Papers; Working Paper ;, 2015)
The paper contributes to the discussions on fiscal governance in Europe. It takes stock of recent reforms, identifies areas for further progress, and discusses a menu of policy options for the medium-term. The issues covered include: (i) the growing complexity of the European framework and ways to simplify it; (ii) the difficulties to measure and implement structural stance indicators; (iii) the challenge of reconciling fiscal sustainability and growth; (iv) the need to enhance coordination in the area of monitoring; and (v) the obstacles to compliance and proposals to strengthen enforcement.